(untitled) (London Journal of Medical and Health Research, 2025)
Chikungunya virus (CHIKV) infection has been linked to severe neurological outcomes, notably Guillain-Barr Syndrome (GBS). This systematic review highlights clinical and mechanistic evidence associating CHIKV with autoimmune polyradiculoneuropathies. Findings reveal the viruss neurotropism and support its role as a triggering factor for GBS. Despite methodological heterogeneity among studies, the evidence underscores important implications for diagnosis, clinical surveillance, and patient management. Deeper understanding of this relationship is essential to improve preventive and therapeutic health strategies.